The Genetic Resources Policy Initiative Newsletter: September 2006 - International Plant Genetic Resources Institute (2006)
In the second quarter of 2006, the GRPI Project registered increased participation from stakeholders and institutions working on country-specific activities designed to support the research and development of law and policy as it relates to PGRFA. The activities which include: Strengthened capacity of domestic governments to 'mainstream' interdepartmental coordination and multi-stakeholder consultation concerning GRFA-related policy-making and implementation; Research papers linking national sectoral activities, socio-economic analysis and development goals to policy options; and Draft national policies are expected to advance in a positive way throughout the remaining part of this year. It is expected that concerted efforts will drive the processes to fruition within the time frame determined under the current institutional framework. Marking a very remarkable achievement during the same quarter, the first meeting of the Governing Body of the International Treaty on Plant Genetic Resources for Food and Agriculture adopted several decisions to help the world community fight global poverty and hunger. Among the most important was the adoption of the standard Material Transfer Agreement (sMTA). The sMTA is a uniform contract that enables easier access to crop biodiversity for farmers and scientists alike. It sets out the terms that govern access and benefit sharing and will accompany all transfers of genetic materials. In this edition of our newsletter, we focus on a number of important activities and events that occurred in GRPI countries and sub regions in the second quarter of the year as well as highlights on new developments in the secretariat. We also include a new section on the current policy trends. In this issue we present an article on the registration of enhanced rice varieties in Nepal. The status of our information sharing initiatives on the internet and networking activities is also highlighted. Information is provided on forthcoming events including the GRPI project wide meeting which is scheduled for early November this year. Finally, we acknowledge with thanks all contributions to this newsletter, especially from our stakeholders in various national programmes who shared the activities they carried out in the immediate past - and which gave us an in-depth insight into the current research course. The purpose of this newsletter is to inform all our national partners and stakeholders of activities and events that are taking place in the Project. The unique design of this newsletter allows for quick and easy access to articles of interest to you. New articles will be added every time we produce the newsletter. Older newsletters will be archived and may be made available upon request. There will be four editions of this newsletter. The purpose of having quarterly editions is to target information that is relevant to your needs. For more information, do not hesitate to contact. As always, we would like to extend our gratitude to all national partners and stakeholders who have played an instrumental role in our efforts aimed at strengthening capacity to analyse national options.